THE EFFECT OF USE OF MULTIPLE REPRESENTATIONS IN SOCIAL SCIENCES CLASS ON THE STUDENTS' ACADEMIC SUCCESS AND ATTITUDES TO THE SOCIAL STUDIES COURSE - Üstün, Sadullah; Karatekin, Kadir (Open Access Publishing Group, 2022)
The learning environment should support students' interest, desire and attitude towards learning. Qualified learning environments will positively affect students' learning situations. For this reason, teachers should use effective learning/teaching approaches in their lessons in order to enrich learning environments. Especially in the social studies course, where the concepts and knowledge of many disciplines are taught with an interdisciplinary approach, teachers should use effective learning/teaching approaches skillfully. One of the approaches that will increase the level of learning in social studies course is multiple representations. The use of multiple representations is an approach that improves students' mental characteristics and is effective in teaching abstract concepts. The aim of this research is to test the effectiveness of teaching practices supported by multiple representation in the social studies course, which includes many abstract concepts. In this study, a quasi-experimental model with pretest-posttest control group was used. In the research, the effect of teaching using multiple representation in social studies teaching on students' academic achievement and attitudes towards social studies lesson was observed. The sample of the research consists of 40 students studying in the 4th grade of primary school. In order to collect data in the research; "The Place We Live In Achievement Test" developed by the researcher and the "Attitude Scale Towards Social Studies Lesson" developed by Arslan and Şahiner (2010) were used. Before the study, the achievement test and the attitude scale were applied to the experimental and control groups as a pre-test. In the five-week period, the control group, with program-based teaching methods; In the experimental group, the lesson was taught with activities prepared with multiple representations. At the end of the process, a post-test was given to the experimental and control groups. As a result of the research, it was concluded that the use of multiple representations positively affected the academic success of the students and their attitudes towards the social studies course. Article visualizations:
Keywords: 4. Education; 3. Good health